Lower Avoidant Coping Mediates the Relationship of Emotional Intelligence With Well-Being and Ill-Being - MacCann, Carolyn; Double, Kit S.; Clarke, Indako E. (Frontiers in Psychology, 2022)
Emotional intelligence (EI) abilities relate to desirable outcomes such as better well-being, academic performance, and job performance. Previous research shows that coping strategies mediate the effects of ability EI on such outcomes. Across two cross-sectional studies, we show that coping strategies mediate the relationships of ability EI with both well-being (life satisfaction, psychological well-being) and ill-being (depression, anxiety, stress). Study 1 (N = 105 first-year university students, 78% female) assessed EI with the Situational Test of Emotion Understanding (STEU) and Situation Test of Emotion Management (STEM). Avoidant coping significantly mediated the relationship of both the STEU and STEM with depression, anxiety, stress, and psychological well-being (but only the STEM with life satisfaction). EI was associated with lower avoidant coping, higher well-being and lower ill-being. Study 2 (N = 115 first-year university students, 67% female) assessed EI with the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT). Again, avoidant coping mediated the relationship between EI and psychological well-being, depression, anxiety, and stress, but not life satisfaction. These effects were significant for all four EI branches—emotion perception, facilitation, understanding, and management. We discuss possible reasons why avoidant coping may be an active ingredient by which lower EI relates to lower well-being. We also discuss a possible application of our findings—that EI training programs might benefit from including content aimed at reducing avoidant coping.